Analysis of Academic Application Acceptance Widya Mandala Catholic University Surabaya Using Method Unified Theory Of Acceptance And Use Of Technology (UTAUT) - Prasetiyo, Hendrik Djoni; Sutomo, Erwin; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The application of akademik.wima.ac.id is a media of information for student, lecture, and administration officer in Widya Mandala Catholic University Surabaya. The application is used to fill Study Plan Card (KRS) and Lecture’s Performance Evaluation Questionnaire; check Grades’ History, Students’ Activity Point, and Study’s Schedule. The result through observation and interview with students from Business Faculty is found out that some information has not been Up to Date and the limitedness access of the application use. The design to find the data of the application is using Unified Theory of Acceptance and Use of Technology (UTAUT) method. Questionnaire is used to collect the data from 334 students of Business Faculty. Microsoft Excel is used to process the data. Descriptive Analysis, Validity and Reliability test is used SPSS 16, and data analysis is used Structural Equation Model (SEM). The result of this study shows the application has a positive and strong acceptance to students. Variables Mean of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavior Intention, and Use Behavior is 76,53% students agree and really agree and often and really often to use the application.